Pain-mediated affect regulation is reduced after dialectical behavior therapy in borderline personality disorder: a longitudinal fMRI study - Niedtfeld, Inga; Bohus, Martin; Schmahl, Christian; Herpertz, Sabine (Social cognitive and affective neuroscience, 2017)
Borderline Personality Disorder (BPD) is characterized by affective instability, but self-injurious behavior appears to have an emotion-regulating effect. We investigated whether pain-mediated affect regulation can be altered at the neural level by residential Dialectical Behavior Therapy (DBT), providing adaptive emotion regulation techniques. Likewise, we investigated whether pain thresholds or the appraisal of pain change after psychotherapy. We investigated 28 patients with BPD undergoing DBT (self-referral), 15 patients with treatment as usual and 23 healthy control subjects at two time points 12 weeks apart. We conducted an fMRI experiment eliciting negative emotions with picture stimuli and induced heat pain to investigate the role of pain in emotion regulation. Additionally, we assessed heat and cold pain thresholds.At first measurement, patients with BPD showed amygdala deactivation in response to painful stimulation, as well as altered connectivity between left amygdala and dorsal anterior cingulate cortex. These effects were reduced after DBT, as compared with patients with treatment as usual. Pain thresholds did not differ between the patient groups. We replicated the role of pain as a means of affect regulation in BPD, indicated by increased amygdala coupling. For the first time, we could demonstrate that pain-mediated affect regulation can be changed by DBT.